Degree of handedness, but not direction, is a systematic predictor of cognitive performance - Prichard, E.; Propper, R. E.; Christman, S. D. (Frontiers in Psychology, 2013)
A growing body of evidence is reviewed showing that degree of handedness (consistent versus inconsistent) is a more powerful and appropriate way to classify handedness than the traditional one based on direction (right versus left). Experimental studies from the domains of episodic memory retrieval, belief updating/cognitive flexibility, risk perception, and more are described.These results suggest that inconsistent handedness is associated with increased interhemispheric interaction and increased access to processes localized to the right cerebral hemisphere.